Strategi dalam Membangun Kembali Kemandirian Pengadilan di Indonesia . - Rusli Muhammad (Fakultas Hukum Universitas Islam Indonesia, 2004)
The independence of the court has been regardedand it has guarantee in constitution, butinaction, especially the action ofcn'minal lawenforcement in Indonesia, the independence of the court is in the lowest rankeven buried. To rebuild the independence of the court, such that, the correlation of the court with other component is unseparable, for instance, structure, regulation,, and personal componentsof the court. With consideration oft hecourt component, the strategy in rebuilding of the independence of the court is donethrough taking reconstnictionofthe court, the reform of regulation and revitalization of the court.